2005
DOI: 10.1002/jbt.20062
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of arsenite activates nuclear factor‐κB and activator protein‐1 in immortalized mesencephalic cells

Abstract: Degeneration of dopaminergic neurons is one of the major features of Parkinson's disease. Many redox-active metals such as iron and manganese have been implicated in neuronal degeneration characterized by symptoms resembling Parkinson's disease. Even though, arsenic, which is another redox-active metal, has been shown to affect the central monoaminergic systems, but its potential in causing dopaminergic cell degeneration has not been fully known. Hence, the present study was designed to investigate arsenic sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 91 publications
4
32
0
1
Order By: Relevance
“…A recent study has shown that As(13) and dopamine synergistically can cause enhanced toxicity in cultured neuronal cells with a dopaminergic phenotype (Shavali and Sens, 2008). Another study suggests that arsenite, at low and nontoxic concentrations, induces oxidative stress leading to activation of early transcription factors in immortalized mesencephalic neurons (Felix et al, 2005). Addition of antioxidants inhibited the activation of these factors.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study has shown that As(13) and dopamine synergistically can cause enhanced toxicity in cultured neuronal cells with a dopaminergic phenotype (Shavali and Sens, 2008). Another study suggests that arsenite, at low and nontoxic concentrations, induces oxidative stress leading to activation of early transcription factors in immortalized mesencephalic neurons (Felix et al, 2005). Addition of antioxidants inhibited the activation of these factors.…”
Section: Discussionmentioning
confidence: 98%
“…IκK has a thiol moiety that may be modified by AsIII leading to IκK activation. However, arsenic-mediated ROS have also been found to promote NFκB-mediated apoptosis [7375]. These opposing findings, though perplexing, may point to the importance of the dose-dependent effects of arsenic.…”
Section: Arsenic Toxicitymentioning
confidence: 99%
“…Cells normally respond to these changes by activating the defense mechanisms to re-establish redox homeostasis and protect from oxidative damage (15,16). We and others have previously reported the transcriptional activation by arsenite of a battery of antioxidant genes, including hemeoxygenase-1, metallothionein 1 and 2, and thioredoxin reductase 1, which may result in parallel changes in protein levels and enzyme or binding activity (17,18).…”
mentioning
confidence: 99%